Disguised Allowance Case in Yassıada: The Expenditures on Press and Official Institutions - Yunus Özdurğun; Bekir Koçlar (Yakın Dönem Türkiye Araştırmaları)
This paper discusses the part of the Disguised Allowance case, which is related to the press and official institutions. The Disguised Allowance case is one of the financial corruption cases brought before the Yassıada court after the May 27 military coup. The Disguised Allowance was the Prime Minister’s initiative, which was to be spent in the interest of the state, and the expenditure information generated under this allowance had to be destroyed together with the receipts. However, the receipts were retained and not destroyed when the Democratic Party was in power. Hence, after May 27, the Supreme Court of Justice examinedThis paper discusses the part of the Disguised Allowance case, which is related to the press and official institutions. The Disguised Allowance case is one of the financial corruption cases brought before the Yassıada court after the May 27 military coup. The Disguised Allowance was the Prime Minister’s initiative, which was to be spent in the interest of the state, and the expenditure information generated under this allowance had to be destroyed together with the receipts. However, the receipts were retained and not destroyed when the Democratic Party was in power. Hence, after May 27, the Supreme Court of Justice examined